: English Language - Herianti, Eva; Marundha, Amor; Nugrahanti, Trinandari Prasetya; Tarigan, Krisnawati; Herninta, Tiwi; Veny, Veny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Effective financial management is crucial for Micro, Small, and Medium Enterprises (MSMEs) to accurately determine business profits and losses and conduct thorough evaluations for strategic decision-making. Many MSMEs struggle with suboptimal financial management due to a limited understanding of accounting principles, financial reporting, planning, and budgeting. To address these challenges, a community service team organized an event titled “Financial Management Education for MSMEs as a Tool to Determine Business Profit and Loss.” Held on June 29, 2024, in Kadudampit Subdistrict, Sukabumi Regency, the event engaged 30 MSME participants from Gede Pangrango Village, Sukamaju Village, and Kadudampit Village. The program included field observations, obtaining necessary permits, and the event execution. Participants underwent a pre-test to assess their initial knowledge, followed by a detailed instructional phase featuring presentations, discussions, and Q&A sessions. Topics covered included fundamental accounting principles, financial reporting, cost of production, pricing strategies, and break-even analysis. The event concluded with a post-test to evaluate knowledge improvements. Results indicated a significant enhancement in participants' understanding of financial management, likely aiding their business development and growth.